PROSPEKTIFITAS PEMBENTUKAN LEMBAGA PERLINDUNGAN DATA PRIBADI DALAM PERSPEKTIF PERLINDUNGAN HAK WARGA NEGARA - Ridho Akbar Utiarahman; Supriyadi A Arief (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
Law No. 27 of 2022 on Personal Data Protection is a strategic step by the Indonesian government to provide a legal basis for protecting public privacy. However, its implementation faces obstacles, particularly related to the absence of an independent supervisory body to ensure that personal data is managed in accordance with adequate security standards. This article reviews the legal aspects of personal data protection against data leaks by government agencies, focusing on the obligations of the state, obstacles to the implementation of the PDP Law, and the importance of establishing an independent supervisory agency. This study uses a normative legal method with a doctrinal approach and literature analysis. The results of the study show that the enactment of Law No. 27 of 2022 on Personal Data Protection is a significant step by the government to provide a clear legal framework for protecting public data. However, major challenges remain in the implementation of this law, particularly regarding the establishment of an independent supervisory agency. Therefore, the establishment of this agency is an effort to realise the protection of citizens' rights.